2004
DOI: 10.1007/s00586-004-0780-7
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on electromyographic analysis of the paraspinal musculature in idiopathic scoliosis

Abstract: The paraspinal muscles have been implicated as a major causative factor in the progression of idiopathic scoliosis. Therefore, the objectives of this preliminary study were to measure the electromyographic activity (EMG) of the paraspinal muscles to determine its relationship to progression of the scoliotic curve. Idiopathic scoliotic patients were selected and identified afterwards on curve progression. The EMG activity on both sides of the spine was measured in a set of standardized postures using bipolar su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 17 publications
8
97
0
2
Order By: Relevance
“…As mentioned earlier, Cheung et al 2,8 found a relationship between curve progression and altered electromyography ratios of the convex and concave sides of the curve. An electromyography was made of the paraspinal muscles in order to determine the ratios of muscle activity on the convex and concave side of the main scoliotic curve.…”
Section: Electromyography Of the Paraspinal Musclesmentioning
confidence: 73%
See 1 more Smart Citation
“…As mentioned earlier, Cheung et al 2,8 found a relationship between curve progression and altered electromyography ratios of the convex and concave sides of the curve. An electromyography was made of the paraspinal muscles in order to determine the ratios of muscle activity on the convex and concave side of the main scoliotic curve.…”
Section: Electromyography Of the Paraspinal Musclesmentioning
confidence: 73%
“…A promising method was shown b y C h e u n g e t a l 2,8 , who found a relationship between curve progression and altered electromyography ratios of the convex and concave sides of the curve. This will be discussed later.…”
Section: Introductionmentioning
confidence: 99%
“…These models are in agreement with emerging evidence from biomechanical and neurophysiologic measures that suggest dysfunction of the neuromuscular system may be an additional factor and indicator of progression risk in IS. This evidence is drawn from studies that have demonstrated increased asymmetry in paraspinal muscle activity [27,28,29], altered sensory weighting [30], and postural control [31]. Of these studies, only a few have focused on identifying the predictive ability of neuromuscular measures [27,28,29].…”
Section: Contemporary Models Of Assessment For Idiopathic Scoliosismentioning
confidence: 99%
“…This evidence is drawn from studies that have demonstrated increased asymmetry in paraspinal muscle activity [27,28,29], altered sensory weighting [30], and postural control [31]. Of these studies, only a few have focused on identifying the predictive ability of neuromuscular measures [27,28,29]. For example, in patients who have IS, the presence of asymmetrical activation of the paraspinal muscles when standing quietly upright has been found to have a 68 % probability of progression, which increases to 80 % when combined with growth velocity [28].…”
Section: Contemporary Models Of Assessment For Idiopathic Scoliosismentioning
confidence: 99%
“…This progression is attributable to biomechanical factors such as modified trunk alignment and body weight influences which create modifications in muscular moments acting on the spine especially during growth spurt [5,17,35,43]. To restore good posture and to prevent scoliosis progression, physiotherapists work on muscle balance.…”
Section: Introductionmentioning
confidence: 99%